KERENDAHAN HATI RELASIONAL DALAM PROSES PEMBELAJARAN MEMPREDIKSI SKEMA RELIGUS PESERTA DIDIK DI DAERAH PASCA KONFLIK - Latuconsina, Adam; Bahiya Gasam (al-Iltizam: Jurnal Pendidikan Agama Islam, 2023)
Lately, research on humility has begun to lead to the world of education. This is because relational humility facilitates a dialogic learning process that positively impacts students, namely the formation of religious schemes. Nonetheless, research on this topic has never been conducted on individuals living in post-interfaith conflict areas. Even though individuals who live in post-conflict areas have formed their humility and religious schemes. Does relational humility strongly predict the emergence of student religious schemas in post-conflict areas? This is the question that is explained in this study. This study used ex-post facto research with a sample of 49 students from four universities in Ambon City. The research data were obtained from the subjects' answers on two scales, namely the Rational Humility Scale (RHS) and the Religious Schema Scale (RSS). The results of a simple linear regression test prove that relational humility also predicts the religious schema of students living in post-religious conflict areas. Nonetheless, the predictive magnitude is minimal due to the limitations of the research sample. Therefore, it is recommended that further researchers consider the size of the research sample and the need to examine relational humility and religious schemas as a mediator or moderator variables for tolerant behavior in the educational context.